The Stringer : independent news. - The Stringer (Fremantle, Western Australia : The Stringer, 2013)
"The Stringer is an independent online news site, delivering free-to-access independent news to readers daily. We went live on February 20 and formally launched on February 25, 2013 at the Media at the Crossroads Conference at NSW Parliament's Theatrette. The Stringer was founded by media academic and producer Jennifer Kaeshagen and by multi-award winning investigative journalist Gerry Georgatos."--About
Title from title screen (viewed on 25 August 2014)
Mode of access: Available online. Address as at 20/10/14
Selected for archiving
Keywords: Aboriginal Australians in mass media; Human rights -- Australia; Mass media and minorities -- Australia; Australian